Labour Mobility - An Adjustment Mechanism in Euroland? - Patrick A. Puhani (Institute for the Study of Labor (IZA), 1999)
The purpose of this paper is to evaluate whether labour mobility is likely to act as a sufficient adjustment mechanism in the face of asymmetric shocks in Euroland. To this end, we estimate the elasticity of migration with respect to changes in unemployment and income on the basis of regional panel data provided by Eurostat, the statistical office of the European Union. Regression results are provided for Western Germany, France, and Italy. It is shown that labour mobility is highest in Germany, followed by France, and Italy. However, even in Germany, the accommodation of a shock to unemployment by migration takes several years. We conclude that labour mobility is extremely unlikely to act as a sufficient adjustment mechanism to asymmetric shocks in Euroland.
Keywords: E66; P52; J61; 330; European Monetary Union (EMU); euro; labour mobility; Europäische Wirtschafts- und Währungsunion; Schock; Wirtschaftliche Anpassung; Arbeitsmobilität; Schätzung; Deutschland; Frankreich; Italien